Analysis of Students' Mathematical Problem-Solving Ability and Semiotics in Terms of Adersity Quotient (AQ) - Supriadi; Irna Rusani; Zakiyah Anwar; Rahmatullah Bin Arshad; Marlinda Indah Eka Budiarti; Yulainti Sira’a (Bulletin of Science Education, 2024)
This study aims to analyze students' problem-solving abilities and mathematical semiotics based on Adversity Quotient (AQ). This qualitative research uses a descriptive approach. The research subjects were selected using an AQ questionnaire and conducted in Class IX F of SMP Negeri 14 Raja Ampat, involving three students divided into three groups. The first group consisted of one climber-type student, the second group included one camper-type student, and the third group included one quitter-type student. Data collection techniques included an AQ questionnaire, tests, and unstructured interviews. Data analysis techniques involved data reduction, data presentation, and conclusion drawing. The research results indicate that an analysis of students' problem-solving abilities and mathematical semiotics based on adversity quotient shows that students in the climber category have excellent problem-solving abilities, meeting all four problem-solving indicators according to Polya's theory. These students also demonstrate an understanding of semiotics from Peirce's perspective, successfully solving problems using this approach. Students in the camper category show moderate problem-solving abilities, meeting three indicators: understanding, planning, and executing the problem-solving process, but lack in reviewing their answers. Regarding semiotics from Peirce's perspective, camper-category students can create signs, identify objects, and interpret signs but struggle to complete the final solution. In contrast, quitter-type students display low problem-solving abilities, failing to meet the problem-solving indicators according to Polya's theory or the semiotic indicators from Peirce's perspective.